Absent Pulmonary Valve: A Case With Rare Presentation Treated With Bioprosthetic Valve Replacement. (October 2014) - Kariyappa, Mallesh; Agrawal, Navin; Srinivas, B. C.; Ravindranath, K. S.; Manjunath, C. N.
Congenital absence of the pulmonary valve is a rare congenital cardiac malformation, usually seen in association with tetralogy of Fallot. Patients generally present early in life with respiratory distress or recurrent respiratory tract infections, failure to thrive, cyanosis, infective endocarditis, or heart failure. Isolated absent pulmonary valve is quite rare and may be discovered in older age-group as in our patient, a nine-year-old male child who presented with atypical symptoms of exertional chest pain. Unusual echocardiographic features in this case include intact ventricular septum and prominent trabeculations of the right ventricle. Surgical implantation of a bioprosthetic valve was followed by hemodynamic and symptomatic improvement.